STRATEGI KRAMA SUBAK DALAM MENANGGULANGI ALIH FUNGSI LAHAN PERTANIAN AKIBAT PARIWISATA (Studi Kasus Subak Umadesa Desa Lodtunduh, Ubud) - Artawan, I Made Jodi; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA, 2016)
The research titled "strategy of subak community in reducing land alternation of ricefields due to tourism (Case Study Subak Umadesa Lodtunduh Village, Ubud)", aims to understand subak strategy in reducing land alternation of ricefields due to tourism in Subak Umadesa, Lodtuduh Village, Ubud, Gianyar-Bali. This research uses SWOT analysis techniques, with data collection techniques of observation, in-depht interviews, literature study, and documentation. Moreover the technique of determining informants using purposive sampling technique, which determines the sample with a certain consideration which is deemed enable to provide the data to the maximum results in accordance with the criteria of the research objectives. The result of this research after conducting interviews and observations based on SWOT analysis matrix is creating agro-ecotourism activities. Forms and types of activities of agro-ecotourism that can be implemend in the territory of Subak Umadesa include: trekking, directly agricultural activities such as plowing, planting, harvesting, interaction with local people directly, etc. Hence the agricultural sector is not being marginalized by the development of activities in tourism sector.
Keywords: Strategy, Subak, Land Alternation, Agro-ecotourism.